PENGARUH DISIPLIN KERJA, GAYA KEPEMIMPINAN, KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT ASIA RECYCLE MANDIRI DI KARANGANYAR - Elida Zia'ul Huda; Endang Winarsih; Ngaisah Ngaisah (STIE Wijaya Mulya, 2023)
The purpose of this research is to find out more deeply about the influence of work discipline, leadership style, compensation and motivation on the performance of employees of PT Asia Recycle Mandiri in Karanganyar. The formulation of the problem found in this study is whether work discipline, leadership style, compensation and motivation have a significant and positive effect on the performance of PT Asia Recycle Mandiri employees in Karanganyar and which of the four variables has the most influence on the performance of PT Asia Recycle employees Independent in Karanganyar. The hypothesis in this study suspects that there is a significant and positive effect of work discipline, leadership style, compensation and motivation on the performance of employees of PT Asia Recycle Mandiri in Karanganyar. And Work Discipline is the variable that has the most positive and significant effect on the performance of employees of PT Asia Recycle Mandiri in Karanganyar. The results of data analysis in this study describe that work discipline, leadership style and compensation have a positive and significant influence on the performance of employees of PT Asia Recycle Mandiri in Karanganyar. However, motivation does not have a positive influence on the performance of employees of PT Asia Recycle Mandiri in Karanganyar. The results of multiple linear regression tests show that the influence of work discipline is 0.224, the influence of leadership style is 0.288, the influence of compensation isÂ 0.370 and the influence of motivation is 0.162 on the performance of employees of PT Asia Recycle Mandiri in Karanganyar. Compensation is the variable that has the most influence on the performance of employees of PT Asia Recycle Mandiri in Karanganyar. This is shown from the calculation of multiple linear regression coefficients (b) = 0.370. This shows that if the compensation variable increases by one unit, while the variables of work discipline, leadership style and motivation are constant at zero or fixed, then employee performance (Y) will increase by 0.370. Keywords: Work Discipline, Leadership Style, Compensation, Motivation andÂ Employee Performance.